Deciphering the Path of S-nitrosation of Human Thioredoxin: Evidence of an Internal NO Transfer and Implication for the Cellular Responses to NO - Vitor S. Almeida; Lara L. Miller; João P. G. Delia; Augusto V. Magalhães; Icaro P. Caruso; Anwar Iqbal; Fabio C. L. Almeida (MDPI AG, 2022)
Nitric oxide (NO) is a free radical with a signaling capacity. Its cellular functions are achieved mainly through S-nitrosation where thioredoxin (hTrx) is pivotal in the S-transnitrosation to specific cellular targets. In this study, we use NMR spectroscopy and mass spectrometry to follow the mechanism of S-(trans)nitrosation of hTrx. We describe a site-specific path for S-nitrosation by measuring the reactivity of each of the 5 cysteines of hTrx using cysteine mutants. We showed the interdependence of the three cysteines in the nitrosative site. C73 is the most reactive and is responsible for all S-transnitrosation to other cellular targets. We observed NO internal transfers leading to C62 S-nitrosation, which serves as a storage site for NO. C69-SNO only forms under nitrosative stress, leading to hTrx nuclear translocation.